2014
DOI: 10.1186/1471-2318-14-66
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of four fear of falling rating scales in people with Parkinson’s disease

Abstract: BackgroundFear of falling (FOF) is commonly experienced in people with Parkinson’s disease (PD). It is a predictor of recurrent falls, a barrier to physical exercise, and negatively associated with health-related quality of life. A variety of rating scales exist that assess different aspects of FOF but comprehensive head-to-head comparisons of their psychometric properties in people with PD are lacking. The aim of this study was to evaluate the psychometric properties of four FOF rating scales in people with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 45 publications
3
59
0
2
Order By: Relevance
“…These observations have important clinical implications. Near falls are more frequent than falls in PD [39, 40] and may occur also among those who do not experience falls [39, 41]. We previously found, in the same project, that history of near falls but not falls was a risk factor for future falls [12].…”
Section: Discussionmentioning
confidence: 99%
“…These observations have important clinical implications. Near falls are more frequent than falls in PD [39, 40] and may occur also among those who do not experience falls [39, 41]. We previously found, in the same project, that history of near falls but not falls was a risk factor for future falls [12].…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be acknowledged that there could be other environmental factors of importance for concerns about falling in people with PD, such as physical environmental barriers, which are not addressed in the present study. Walking on slippery surfaces was in fact ranked as the most difficult FES-I item in a previous PD study [6], and difficulties climbing stairs have been shown to be of importance for fall-related self-efficacy [12]. Accordingly, further research on the possible impact of physical environmental factors on FOF in people with PD by using more detailed data on housing and close exterior surroundings is motivated, but due to the methodological complexity of such issues specific studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…The FES-I (i.e., our dependent variable) was developed by combining and modifying three other FOF scales [2], of which two are based on Bandura's theory of self-efficacy [3,4]. Although FES-I scores have been shown to correlate (r > 0.80) with self-efficacy based FOF measures [6], the findings in the present study suggest that concerns about falling are not strongly connected to general self-efficacy in people with PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations